Bromelain‐based enzymatic debridement of chronic wounds: Results of a multicentre randomized controlled trial. Issue 6 (7th July 2021) - Shoham, Yaron; Shapira, Eyal; Haik, Josef; Harats, Moti; Egozi, Dana; Robinson, Dror; Kogan, Leonid; Elkhatib, Rania; Telek, Geza; Shalom, Avshalom
Abstract: Chronic wounds are estimated to affect over 6 million people annually in the United States with an estimated annual cost of $25 billion. Debridement represents a key step in their management and is considered a basic necessity to induce the functional process of tissue repair. However, there is an unmet need for an efficient rapid acting non‐surgical debridement agent. Bromelain‐based enzymatic debridement has been proven to provide an effective, selective and safe non‐surgical debridement in deep burns. EscharEx (MediWound Ltd, Yavne, Israel), is a bromelain‐based enzymatic debridement agent currently in development for chronic wounds. The aim of this study was to assess its safety and efficacy in chronic wounds. Seventy‐three patients suffering from a lower extremity ulcer of diabetic/venous insufficiency/post‐surgical/traumatic aetiology were enrolled in a multicentre, assessor blinded, randomized controlled trial. Patients were randomized to topical treatment by either EscharEx or its gel vehicle for up to 10 daily 4 hour applications, and then continued follow‐up for up to 6 months. The EscharEx arm achieved a significantly higher incidence of complete debridement compared to the gel vehicle arm; 55 versus 29% ( p  = .047), thus meeting the primary endpoint of this study. The EscharEx and gel vehicle arms achieved similar reductions in wound area, non‐viable tissue area and wound healing scores during the debridement period. There were no significant differences between the arms in the incidence of complete wound closure (41% in the EsxcharEx arm vs. 53% in the gel vehicle arm) and in the mean time to complete wound closure (70.0 ± 32.8 days in the EsxcharEx arm vs. 65.7 ± 38.4 days in gel vehicle arm). There were no significant safety issues and EscharEx demonstrated a favourable benefit to risk profile.